Determinación del comportamiento de la humedad presente en los suelos de dos Parroquias Rurales del Cantón Latacunga ( Aláquez y San Buenaventura) en el período 2010-2012 mediante teledetección - Chiluisa Tipanluisa, Mariela Sthefania (2017)
The present investigation has as purpose to determine the behavior of the humidity present in the soil of two rural parishes, Alàquez and San Buenaventura during 2010 – 2012 period in Latacunga Canton, Cotopaxi Province , the data of humidity of the Weather stations of Cotopaxi - Clirsen, El Corazon, Izobamba, La Victoria INERHI, Quito INAMHI - INNAQUITO and, Rumipamba – Salcedo, was to taken identify the zones that contain the best percentages of humidity in the areas proposed . First of all, the data were analyzed statistically and with Lasnsadt satellite images performing the interpolation with the tool (IDW), through a weighted inverse distance wich determines the cell values through a weighted combination thus obtaining qualitative and quantitative results respectively, where the values were humidity identified in three ranges: 1.- High Humidity between 83.4 to 88.7%, which is located in the high zones of Aláquez it means paramos. 2.- Average Humidity between 74.7% and 81.7% which are located in the areas of Alaquez and San Buenaventura, 3.- Low Humidity between 67.7% and 72.9%, which is located in the lower areas of Aláquez and San Buenaventura, which is corroborated by the statistical analysis of the meteorological stations that give a result of humidity between 74.2% and 89.02%. However, the Cotopaxi Clirsen meteorological station was not taken into account in the interpolation of the data because it is in a protected area where there is no anthropogenic intervention, wich means that the habitats are in their natural state, where the statistical analyzes carried out with a percentage of 96.5% of humidity was obtained.